Genomic attributes and characterization of novel exopolysaccharide-producing bacterium Halomonas piscis sp. nov. isolated from jeotgal - Kim, Bora; Yang, Ah-In; Joe, Hae-In; Kim, Ki Hyun; Choe, Hanna; Joe, Sung-Hong; Jun, Min Ok; Shin, Na-Ri (Frontiers in Microbiology, 2023)
Halophilic bacterial strains, designated SG2L-4 T , SB1M4, and SB2L-5, were isolated from jeotgal, a traditional Korean fermented food. Cells are Gram-stain-negative, aerobic, non-motile, rodshaped, catalase-positive, and oxidase-negative. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that strain SG2L-4 T is closely related to Halomonas garicola KACC 18117 T with a similarity of 96.2%. The complete genome sequence of strain SG2L-4 T was 3,227,066 bp in size, with a genomic G+C content of 63.3 mol%. The average nucleotide identity and digital DNA-DNA hybridization values between strain SG2L-4 T and H. garicola KACC 18117 T were 90.5% and 40.7%, respectively. The optimal growth conditions for strain SG2L-4 T were temperatures between 30-37℃, a pH value of 7, and the presence of 10% (w/v) NaCl. The polar lipids identified included diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, an unknown phospholipid, an unknown glycolipid, and an unknown polar lipid. The major cellular fatty acids were C16:0, summed features 8 (C18:1 ω6c and/or C18:1 ω7c), C19:0 cyclo ω8c, and summed features 3 (C16:1 ω6c and/or C16:1 ω7c). The predominant respiratory quinone was ubiquinone with nine isoprene units (Q-9). Based on the phenotypic, genotypic, and chemotaxonomic results, strain SG2L-4 T represents a novel species within the genus Halomonas, for which the name Halomonas piscis sp. nov. is proposed. The type strain is SG2L-4 T (=KCTC 92842 T =JCM 35929 T ). Functional annotation of the genome of strain SG2L-4 T confirmed the presence of exopolysaccharide synthesis protein (ExoD) and capsular polysaccharide-related genes. Strain SG2L-4 T also exhibited positive results in Molisch's test, indicating the presence of extracellular carbohydrates and exopolysaccharides (EPS) production. These findings provide valuable insights into the EPSproducing capabilities of H. piscis sp. nov. isolated from jeotgal, contributing to understanding its potential roles in food and biotechnological applications.